ACTN3 R577X and ACE I/D gene variants influence performance in elite sprinters: A multi-cohort study - Papadimitriou, I. D.; Lucia, A.; Pitsiladis, Y. P.; Pushkarev, V. P.; Dyatlov, D. A.; Orekhov, E. F.; Artioli, G. G.; Guilherme, J. P. L. F.; Lancha Jr, A. H.; Gineviciene, V.; Cieszczyk, P.; Maciejewska-Karlowska, A.; et al. (BMC Genomics, 2016)
Background: To date, studies investigating the association between ACTN3 R577X and ACE I/D gene variants and elite sprint/power performance have been limited by small cohorts from mixed sport disciplines, without quantitative measures of performance. Aim: To examine the association between these variants and sprint time in elite athletes. Methods: We collected a total of 555 best personal 100-, 200-, and 400-m times of 346 elite sprinters in a large cohort of elite Caucasian or African origin sprinters from 10 different countries. Sprinters were genotyped for ACTN3 R577X and ACE ID variants. Results: On average, male Caucasian sprinters with the ACTN3 577RR or the ACE DD genotype had faster best 200-m sprint time than their 577XX (21.19 ± 0.53 s vs. 21.86 ± 0.54 s, p = 0.016) and ACE II (21.33 ± 0.56 vs. 21.93 ± 0.67 sec, p = 0.004) counterparts and only one case of ACE II, and no cases of ACTN3 577XX, had a faster 200-m time than the 2012 London Olympics qualifying (v s. 12 qualified sprinters with 577RR or 577R X genotype). Caucasian sprinters with the ACE DD genotype had faster best 400-m sprint time than their ACE II counterparts (46.94 ± 1.19 s vs. 48.50 ± 1.07 s, p = 0.003). Using genetic models we found that the ACTN3 577R allele and ACE D allele dominant model account for 0.92 % and 1.48 % of sprint time variance, respectively. Conclusions: Despite sprint performance relying on many gene variants and environment, the % sprint time variance explained by ACE and ACTN3 is substantial at the elite level and might be the difference between a world record and only making the final.